Synthesis of Axially Chiral Carboxamides via Aminocarbonylation of Aryl and Vinyl Iodides with 2,2'-Diamino-1,1'-binaphthalene in the Presence of Palladium Catalysts - Pálinkás Noémi (CHEMISTRYSELECT, 2020)
Palladium-catalysed aminocarbonylation of iodobenzene and 1-iodocyclohexene with both enantiomerically pure and racemic 2,2'-diamino-1,1'-binaphthalene (BINAM) asN-nucleophile was carried out. The mono- and dicarboxamide enantiomers possessing axial chirality were synthesised using (S-ax)-BINAM. In the possession of these reference compounds the partial chiral kinetic resolution of racemic BINAM was carried out using various optically active bidentate ligands such as (2S,4S)-BDPP, (2S,3S)-CHIRAPHOS and (R)-BINAP. It was revealed by chiral HPLC measurements that up to 10 % enantiomeric excess of carboxamides can be achieved in this way. Although with low enantioselection, enantioselectve aminocarbonylation was carried out for the first time.